The Effect of Product Quality, Service, Brand Image, and Availability on Customer Loyalty with Satisfaction as a Mediation Variable (Study at Astra Isuzu Harapan Indah) - Muhammad Irfan Rizki; Fansuri Munawar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines the effect of product quality, service quality, brand image, and spare part availability on customer loyalty, with customer satisfaction as a mediating variable. The research involved customers of Dealer AI Harapan Indah who had used its services and purchased spare parts in the past two years. A quantitative approach was applied using purposive sampling of 300 respondents, and data were analyzed with the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results indicate that product quality (p-value= 0.000), service quality (p-value = 0.004), brand image (p-value = 0.010), and spare part availability (p-value = 0.001) have significant positive effects on customer satisfaction. Customer loyalty is directly influenced by product quality (p-value = 0.026) and customer satisfaction (p-value = 0.004), while spare part availability, service quality, and brand image affect loyalty indirectly through satisfaction. Product quality is the most dominant factor in shaping loyalty, aligning with commercial vehicle users’ emphasis on reliability and durability. These findings underscore the importance of improving product reliability, ensuring consistent after-sales service, maintaining brand perception, and securing sustainable spare part availability to strengthen long-term customer loyalty.